1992
DOI: 10.1152/ajpendo.1992.262.2.e135
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of ANP with endothelin on cardiovascular, renal, and endocrine function

Abstract: To assess the interaction of endothelin (ET) with atrial natriuretic peptide (ANP) on cardiovascular and renal function, arginine vasopressin (AVP) release, and the renin-angiotensin-aldosterone system, either a low or high dose of ET (4 or 12 pmol.kg-1.min-1) was administered with ANP (26 pmol.kg-1.min-1) for 45 min after the initial infusion of ANP alone in anesthetized dogs. In the other groups, either ANP or saline alone was administered for 90 min. ANP alone decreased blood pressure (BP), cardiac output (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 3 publications
2
11
1
Order By: Relevance
“…Experimental data have shown that plasma ANP rises after infusion of ET-1 but it remains uncertain to what extent the concomitant rise in blood pressure after ET-1 infusion or a direct stimulatory action of ET-1 on ANP release of cardiomyocytes is responsible for this increase (25). In the present study no correlation between plasma ET-1 and ANP could be found.…”
Section: Discussioncontrasting
confidence: 76%
“…Experimental data have shown that plasma ANP rises after infusion of ET-1 but it remains uncertain to what extent the concomitant rise in blood pressure after ET-1 infusion or a direct stimulatory action of ET-1 on ANP release of cardiomyocytes is responsible for this increase (25). In the present study no correlation between plasma ET-1 and ANP could be found.…”
Section: Discussioncontrasting
confidence: 76%
“…4F). It is known that the endothelin system not only stimulates the secretion of Nppa (52) but that they also counteract each other in some cardiovascular, renal, and endocrine functions (53). Furthermore, previous studies have also demonstrated that Nppa secretion occurs via an EDNRB-mediated pathway involving the MAPK signaling pathway (54), and MAPK along with PI3K pathways regulate the hypoxia-induced Nppa secretion by controlling HIF-1α (55).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II downregulates NP receptors [24] to decrease cGMP production evoked by ANP [25] . Infusion of a high dose of endothelin after ANP infusion curtails the response to ANP, and induces a fall in renal blood flow and GFR [26] . Furthermore, the synthesis of angiotensin II and endothelin was increased in the cortex in GM-induced nephropathy [27,28] .…”
Section: Discussionmentioning
confidence: 99%